Development of 13-Cys-BBR as an Agent Having Dual Action of Anti-Thrombosis and Anti-Inflammation - Li G; Wang T; Zhang X; Zhao S; Wang Y; Wu J; Peng S; Zhao M (Dove Medical Press, 2020)
Guanyu Li,1,2 Tong Wang,1,2 Xiaoyi Zhang,1,2 Shurui Zhao,1,2 Yaonan Wang,1,2 Jianhui Wu,1,2 Shiqi Peng,1,2 Ming Zhao1– 3 1Beijing Area Major Laboratory of Peptide and Small Molecular Drugs, Department of Medicinal Chemistry, School of Pharmaceutical Sciences, Capital Medical University, Beijing 100069, People’s Republic of China; 2Engineering Research Center of Endogenous Prophylactic of Ministry of Education of China, Department of Medicinal Chemistry, School of Pharmaceutical Sciences, Capital Medical University, Beijing 100069, People’s Republic of China; 3Beijing Laboratory of Biomedical Materials and Key Laboratory of Biomedical Materials of Natural Macromolecules, Department of Biomaterials, College of Materials Science and Engineering, Beijing University of Chemical Technology, Beijing 100026, People’s Republic of ChinaCorrespondence: Shiqi Peng; Ming ZhaoDepartment of Medicinal Chemistry, School of Pharmaceutical Sciences, Capital Medical University, NO. 10, Youanmenwaixitoutiao, Fengtai District, Beijing 100069, People’s Republic of ChinaTel +861083911528; +861083911535 Fax +861083911528; +861083911533 Email sqpeng@bjmu.edu.cn; maozhao@126.comBackground: There is a correlation between tumor and inflammation. The activity of 13-[CH2CO-Cys(Bzl)-OBzl]-berberine (13-Cys-BBR) slowing tumor growth is higher than that of BBR. Whether the anti-inflammation activity of 13-Cys-BBR is higher than that of BBR remains unknown. There is a correlation between thrombosis and inflammation. Whether 13-Cys-BBR is an inhibitor of thrombosis remains unknown.Purpose: The object of this investigation is to compare the activities of 13-Cys-BBR inhibiting thrombosis and inflammation to those of BBR.Methods: In vivo anti-thrombosis assay was performed on rat model of arterial and venous thrombosis. In vivo anti-inflammation assay was performed on mouse model of xylene induced ear edema.Results: At oral dose of 66.7 nmol/kg, 13-Cys-BBR, but not BBR, inhibited the rats to form both venous thrombus and arterial thrombus. At oral dose of 2 μmol/kg, 13-Cys-BBR, but not BBR, inhibited the ears of the mice to occur edema.Conclusion: The anti-venous thrombosis activity, anti-arterial thrombosis activity and anti-inflammation activity of 13-Cys-BBR were significantly higher than those of BBR. 13-Cys-BBR is a promising preclinical candidate.Keywords: berberine, 13-Cys-BBR, thrombosis, inflammation